An enterprise structure approach improves index-based crop portfolio decision-making - Mzyece, Agness; Amanor-Boadu, Vincent; Ng'ombe, John N. (Frontiers in Environmental Economics, 2023)
We compare the potential costs of crop diversification based on the measurement of crop diversification using the Simpson index versus using the enterprise structure approach. Results show that recommendations based on the enterprise structure approach result in higher profitability than those based on the Simpson index. Compared to the enterprise structure approach, recommendations from the Simpson index can result in opportunity costs as high as 77.89% in increase in foregone profitability for farmers. These results suggest that the use of aggregation crop diversification indices in applied economics may obscure the necessary insights needed to practically help farmers.